Ternary composite material based on poly-m-toluidine doping as well as preparation method and application of ternary composite material

Through the improved Hummers method, graphene oxide was prepared and nanoferrous tetraoxide formed on its surface, and a ternary composite material based on polymethylene toluidine doping was prepared, which solved the reflection loss of existing absorber materials. The problems of low value and poor matching thickness achieve excellent wave absorption performance in the range of 2-18GHz.

CN119401136APending Publication Date: 2025-02-07HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411516904.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing absorber materials have low reflection loss values ​​and poor matching thicknesses, so they cannot achieve high reflection loss values ​​and good matching thicknesses at the same time.

Method used

Graphene oxide was prepared by the improved Hummers method and polym-toluidine-encapsulated nanoferrous tetroxide was formed on its surface by in-situ polymerization to prepare a ternary composite material based on polym-toluidine doping.

Benefits of technology

The composite material exhibits excellent absorbance performance in the range of 2-18GHz, with a minimum reflection loss at 1.5mm of -52.39dB, an absorption bandwidth of less than -10dB is greater than 4.6GHz, and can fully cover the range of 2-18GHz.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119401136A_ABST
    Figure CN119401136A_ABST
Patent Text Reader

Abstract

The invention discloses a poly-m-toluidine doping-based ternary composite material as well as a preparation method and application thereof, and belongs to the field of electromagnetic wave absorbing materials. The preparation method comprises the following steps: firstly, preparing graphene oxide by adopting an improved Hummers method, and then forming nano ferroferric oxide wrapped by poly-m-toluidine on the surface of the graphene oxide by adopting an in-situ polymerization method to obtain the poly-m-toluidine doping-based ternary composite material. The prepared composite material has excellent wave absorbing performance, the lowest reflection loss at 1.5 mm is-52.39 dB, the absorption band width smaller than-10 dB is larger than 4.6 GHz, the composite material shows excellent wave absorbing performance within the range of 2-18 GHz, and the composite material has huge advantages in the aspects of RL, EAB and matching thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and relates to a ternary composite material doped with poly-meta-toluidine, and a preparation method and application thereof. Background Art

[0002] The rapid development and widespread application of various modern electronic wireless devices have brought great convenience to people's lives and studies, but the consequence is the serious electromagnetic pollution and other unpredictable risks caused by the use of a large number of electronic devices. In order to cope with this risk, research in the field of absorbing materials has aroused widespread research interest in recent years. Absorbing materials are generally composed of a variety of materials, and they achieve good absorption and loss effects on electromagnetic waves under the combined effects of dielectric loss, magnetic loss and relaxation loss.

[0003] As a well-studied magnetic oxide, ferroferric oxide exhibits relatively high magnetic permeability, resistivity and coercivity at high frequencies, which makes it widely studied as an efficient microwave absorbing material. However, due to its high density, this characteristic makes its application range narrow. Composite ferroferric oxide with other absorbing materials will be a potential research direction. Graphene oxide is a unique two-dimensional conductive material that has emerged in recent years. Its excellent absorbing performance comes from its good conductivity. However, due to the high carrier mobility of graphene oxide, it cannot effectively meet the impedance matching mechanism. Conductive polymer is a material with the advantages of low density, easy processing and low cost. It has great advantages in the field of electromagnetic shielding and microwave absorption. Studies have shown that composite graphene oxide with conductive polymers can effectively improve impedance matching and enhance its absorbing performance.

[0004] At present, the research on the preparation of multi-component composite microwave absorbing materials with conductive polymers (such as polyaniline, polypyrrole and polythiophene, etc.) and other materials has attracted widespread attention. For example, the Chinese patent application document with publication number CN108587159A discloses a graphene-like carbon nitride / ferroferric oxide / polyaniline nanocomposite absorbing material and its preparation method. The maximum peak value of the reflection loss of the material at 2-4GHz reaches -50dB. The invention patent with publication number CN116355589A reports a graphene-based ternary composite absorber and absorbing material. The maximum reflection loss of the material in the test frequency range of 2-18GHz is -41.52dB, but the corresponding material matching thickness is 2.3mm. Therefore, the existing absorbing materials cannot achieve a high reflection loss value and a better matching thickness at the same time, so it needs further improvement. Summary of the invention

[0005] The technical problem to be solved by the present invention is how to solve the problems of low reflection loss value and poor matching thickness existing in existing absorbing materials.

[0006] The present invention solves the above technical problems through the following technical means:

[0007] The first aspect of the present invention provides a method for preparing a ternary composite material doped with poly-m-toluidine, comprising the following steps:

[0008] (1) preparing graphene oxide using graphite;

[0009] (2) Graphene oxide, nano-ferroferric oxide, ammonium persulfate, and HCl aqueous solution are uniformly mixed, and then m-toluidine is added to react to fully polymerize, and then washed, dried, and calcined to obtain a ternary composite material based on poly-m-toluidine doping.

[0010] Preferably, in step (1), an improved Hummers method is used to prepare graphene oxide, specifically: graphite, sodium nitrate, and protonic acid are mixed, potassium permanganate is added under an ice bath, the water bath temperature is increased, water is added and stirred, and then hydrogen peroxide is added, the mixture is allowed to stand, washed, and freeze-dried to obtain graphene oxide.

[0011] Preferably, the protonic acid is one or more of concentrated sulfuric acid, hydrochloric acid, acetic acid and oxalic acid.

[0012] Preferably, the ice bath temperature is less than 5°C.

[0013] Preferably, the water bath temperature is 45-65°C.

[0014] Preferably, the washing is performed by centrifugation multiple times using deionized water and ethanol until the pH of the effluent is ≈ 7.

[0015] Preferably, in step (2), the mass ratio of graphene oxide to nano-iron tetroxide is 1:(5-20).

[0016] Preferably, in step (2), the molar ratio of ammonium persulfate to m-toluidine is 1:1.

[0017] Preferably, the drying temperature in step (2) is 50-70° C., and the drying time is 20-28 h.

[0018] Preferably, the calcination temperature in step (2) is 750-850° C., and the calcination time is 1.5-2.5 h.

[0019] The second aspect of the present invention proposes a ternary composite material based on poly-meta-toluidine doping prepared by the above-mentioned preparation method.

[0020] The third aspect of the present invention proposes the use of the above-mentioned ternary composite material as an absorbing material in the field of electromagnetic protection and radar stealth.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention firstly adopts the improved Hummers method to prepare graphene oxide, and then adopts the in-situ polymerization method to form nano-iron tetroxide wrapped with poly-m-toluidine on the surface of the graphene oxide to obtain a ternary composite material based on poly-m-toluidine doping.

[0023] 2. The composite absorbing material exhibits excellent absorbing performance in the range of 2-18 GHz. The minimum reflection loss at 1.5 mm is -52.39 dB, and the absorption band width less than -10 dB is greater than 4.6 GHz. The range of 2-18 GHz can be fully covered by adjusting the matching thickness. Therefore, the composite material has great advantages in RL, EAB and matching thickness.

[0024] 3. Due to the excellent magnetic loss brought by the strong magnetism of ferroferric oxide in the composite material, the high dielectric loss brought by the excellent electrical conductivity of graphene oxide, and the defects of poor impedance matching and narrow absorption band are optimized by ferroferric oxide wrapped by poly-m-toluidine, the absorption bandwidth of the composite material is improved. During the high-temperature calcination process, a large number of oxygen defects appear on the surface of graphene oxide in the material, which increases the multiple scattering and reflection loss of electromagnetic waves, further enhancing the impedance matching of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the poly-m-toluidine-doped ternary composite absorbing material prepared in Example 1;

[0026] Figure 2 It is a two-dimensional reflection loss diagram of the poly-m-toluidine-doped ternary composite absorbing material prepared in Example 1. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0029] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0030] Embodiment 1:

[0031] A method for preparing a ternary composite material doped with poly-meta-toluidine comprises the following steps:

[0032] (1) Prepare graphene oxide using the improved Hummers method: Add 5.0g of graphite and 2.5g of sodium nitrate to a three-necked flask, add 120mL of concentrated sulfuric acid, and stir in a water bath at 2.5rps. Keep the temperature below 5°C in an ice bath. Under this condition, slowly add 3.0g of potassium permanganate every 6min, for a total of 15.0g. Adjust the water bath temperature to 50°C, stir at 2.5rps for 6h, then slowly add 300mL of water to the three-necked flask, then transfer the solution to a beaker and add deionized water to 2.0L, add 200mL of hydrogen peroxide, at which point the suspension changes from dark brown to gold, and let stand overnight to precipitate. Use deionized water and HCl to wash by centrifugation multiple times until the pH of the supernatant is ≈ 7. Freeze-dry for 48h to obtain graphene oxide.

[0033] (2) Weigh 2.28 g of ammonium persulfate as an oxidant, add it into 20 mL of 1 mol / L HCl aqueous solution, sonicate to fully dissolve it, and place the resulting solution in an ice water bath to maintain the temperature at 0-5°C.

[0034] (3) 0.06 g GO and 0.6 g nano-ferroferric oxide were added to 80 mL 1 mol / L HCl aqueous solution and mixed thoroughly by ultrasonication for 20 min. Then, the mixture was added to the solution in step (2) and stirred by electromagnetic stirring for 30 min to mix thoroughly.

[0035] (4) 1.07 g of m-toluidine (in a molar ratio of 1:1 to ammonium persulfate) was slowly added dropwise to the mixed solution of step (3) and reacted for 15 h to allow for full polymerization. After the reaction was completed, the mixture was washed with deionized water and anhydrous ethanol several times until the effluent was neutral, and the obtained solid was dried in a constant temperature drying oven at 60° C. for 24 h.

[0036] (5) The powder obtained in step (4) is placed in a tubular furnace and heated to 800° C. at a temperature program of 5° C. / min under an argon-hydrogen atmosphere, and then maintained for two hours and then cooled to obtain a ternary composite material based on poly-m-toluidine doping.

[0037] The SEM image of the poly-m-toluidine-doped ternary composite material prepared in Example 1 is as follows: Figure 1As shown in the figure, it can be seen that under the action of ammonium persulfate, m-toluidine is in-situ polymerized on graphene oxide, and at the same time, nano-scale ferroferric oxide is attached to the surface of graphene oxide through electrostatic action, which enhances the magnetic loss capacity of the composite material. After high-temperature calcination, a large number of wrinkles appear on the surface of the flake graphene oxide. At the same time, the high temperature causes a large number of oxygen vacancies on the surface of graphene oxide, which increases the scattering sites of electromagnetic waves, enhances multiple scattering, prolongs the propagation path of electromagnetic waves, and improves the microwave absorption capacity.

[0038] Electromagnetic wave absorption performance test method:

[0039] The sample (the ternary composite material based on poly-m-toluidine doping prepared in Example 1) was mixed with paraffin wax at a mass ratio of 4:6 and compacted into a ring with an outer diameter of 7.00 mm and an inner diameter of 2.50 mm. The dielectric constant and magnetic permeability of the sample in the range of 2-18 GHz were then tested using a vector network analyzer. Finally, the wave absorption performance of the sample was obtained by calculation.

[0040] The electromagnetic wave absorption performance of the ternary composite material based on poly-m-toluidine doping prepared in Example 1 at a filling amount of 40 wt% is as follows: Figure 2 shown; from Figure 2 It can be seen that the ternary composite material prepared in this embodiment has excellent wave absorbing performance.

[0041] Embodiment 2:

[0042] The difference between this embodiment and embodiment 1 is that: in step (3), GO is 0.03 g; in step (4), the obtained solid is dried in a 50° C. constant temperature drying oven for 28 h; in step (5), the temperature is raised to 850° C. and maintained for 1.5 h before cooling. The rest is the same as in embodiment 1.

[0043] Embodiment 3:

[0044] The difference between this embodiment and embodiment 1 is that: in step (3), GO is 0.09 g; in step (4), the obtained solid is dried in a 70°C constant temperature drying oven for 20 h; in step (5), the temperature is raised to 750°C and maintained for 2.5 h before cooling. The rest is the same as in embodiment 1.

[0045] Embodiment 4:

[0046] The difference between this embodiment and embodiment 1 is that the amount of nano-iron tetroxide in step (3) is 0.3 g, and the rest is the same as embodiment 1.

[0047] Embodiment 5:

[0048] The difference between this embodiment and embodiment 1 is that the amount of nano-iron tetroxide in step (3) is 0.9 g, and the rest is the same as embodiment 1.

[0049] Comparative Example 1:

[0050] The difference between this comparative example and Example 1 is that GO is not added in step (3), and the rest is the same as Example 1.

[0051] Comparative Example 2:

[0052] The difference between this comparative example and Example 1 is that ferrosoferric oxide is not added in step (3), and the rest is the same as Example 1.

[0053] Comparative Example 3:

[0054] The difference between this comparative example and Example 1 is that GO and ferrosoferric oxide are not added in step (3), and the rest is the same as Example 1.

[0055] Group Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 RL(dB) -52.39 -28.73 -37.62 -33.12 -34.12 -9.53 -16.73 -5.92 <![CDATA[E a (GHz)]]> 4.9 3.4 3.8 2.3 3.5 1.6 2.9 3.5

[0056] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a ternary composite material based on poly-m-toluidine doping, characterized in that: The following steps are involved: (1) preparing graphene oxide using graphite; (2) Graphene oxide, nano-ferroferric oxide, ammonium persulfate, and HCl aqueous solution are uniformly mixed, and then m-toluidine is added to react to fully polymerize, and then washed, dried, and calcined to obtain a ternary composite material based on poly-m-toluidine doping.

2. The method for preparing the ternary composite material based on poly-meta-toluidine doping according to claim 1, characterized in that: In step (1), graphene oxide is prepared using an improved Hummers method, specifically, graphite, sodium nitrate, and protonic acid are mixed, potassium permanganate is added under an ice bath, the water bath temperature is increased, water is added and stirred, and then hydrogen peroxide is added, the mixture is allowed to stand, washed, and freeze-dried to obtain graphene oxide.

3. The method for preparing the ternary composite material based on poly-meta-toluidine doping according to claim 2, characterized in that: The protonic acid is one or more of concentrated sulfuric acid, hydrochloric acid, acetic acid and oxalic acid.

4. The method for preparing the ternary composite material based on poly-meta-toluidine doping according to claim 2, characterized in that: The temperature of the ice bath is less than 5°C, and the temperature of the water bath is 45-65°C.

5. The method for preparing the ternary composite material based on poly-meta-toluidine doping according to claim 1, characterized in that: In step (2), the mass ratio of graphene oxide to nano-iron tetroxide is 1:(5-20).

6. The method for preparing the ternary composite material based on poly-m-toluidine doping according to claim 1, characterized in that: In step (2), the molar ratio of ammonium persulfate to m-toluidine is 1:

1.

7. The method for preparing the ternary composite material based on poly-meta-toluidine doping according to claim 1, characterized in that: The drying temperature in step (2) is 50-70° C. and the drying time is 20-28 hours.

8. The method for preparing the ternary composite material based on poly-m-toluidine doping according to claim 1, characterized in that: The calcination temperature in step (2) is 750-850° C., and the calcination time is 1.5-2.5 h.

9. The ternary composite material based on poly-meta-toluidine doping obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the poly-meta-toluidine-doped ternary composite material as claimed in claim 9 as an absorbing material in the fields of electromagnetic protection and radar stealth.

Citation Information

Patent Citations

  • Graphene-like carbon nitride / ferroferric oxide / polyaniline nano composite wave-absorbing material and preparation method thereof

    CN108587159A

  • Graphene-based ternary composite wave-absorbing agent and wave-absorbing material

    CN116355589A